2013
DOI: 10.1111/apa.12504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body position on preterm newborns receiving continuous positive airway pressure

Abstract: We found no preferential decubitus position for preterm newborns receiving nasal CPAP, the supine position may be a choice, but the left and right lateral positions were less advantageous in terms of oxygen saturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
3
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
2
14
3
4
Order By: Relevance
“…Compared to supine, lateral positioning did not have a significant effect on breathing frequency or tidal volume. Our finding on breathing frequency is consistent with previous studies . However, the data on tidal volume are in contrast to a previous study that reported a significant increase in tidal volume after changing from supine to left lateral position .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Compared to supine, lateral positioning did not have a significant effect on breathing frequency or tidal volume. Our finding on breathing frequency is consistent with previous studies . However, the data on tidal volume are in contrast to a previous study that reported a significant increase in tidal volume after changing from supine to left lateral position .…”
Section: Discussionsupporting
confidence: 90%
“…Our finding on breathing frequency is consistent with previous studies. 5,22 However, the data on tidal volume are in contrast to a previous study that reported a significant increase in tidal volume after changing from supine to left lateral position. 5 It is unclear why our results are different, but factors that may play a role are differences in patient characteristics, study design and the method of measuring tidal volume changes.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…YYBÜ'de yatan prematüre bebeklere MV süresince, MV'den ayırma sırasında ve sonrasında farklı pozisyonlarda yatırmanın solunum fonksiyonlarını etkilediği yapılan bazı çalışmalarda göste-rilmiştir (Tablo 1). 11,29,[30][31][32][33][34][35][36][37][38] Bebeği pron pozisyonda yatırma solunum fonksiyonlarına, özellikle oksijenlenmede artışa, ekspire edilmiş CO 2 'de azalmaya, diyafram kompliyans ve fonksiyonunda artmaya ve toraks-batın asenkronizayonunda azalmaya katkı sağlayabilmektedir. 30 Balaguer ve ark.…”
Section: Mekani̇k Venti̇lasyon Uygulanan Prematüre Bebeklere Pozi̇syon Vunclassified
“…33 Yukarıdaki çalışmalardan farklı olarak, sürekli pozitif havayolu basıncı [continous positive airway pressure (CPAP)] uygulanan prematüre bebeklerle yapılan bir çalışmada; supin, pron ve yan pozisyonda yatan bebeklerin solunum hızları ortalamaları arasında fark bulunmamıştır. 35 Yapılan bir başka çalışmada ise CPAP uygulanan prematüre bebeklere uygulanan pozisyonun etkisiyle oluşan yer çekiminin, bölgesel ventilasyon dağılımları üzerine çok az etkisinin olduğu, fakat pron pozisyonda yatan bebeklerin solunum hızlarının daha az, oksijen satürasyonlarının ve FiO 2 'lerinin daha iyi olduğu bulunmuştur. Buna göre, pron pozisyonda oksijenlenmenin daha iyi olduğu belirtilmiştir.…”
Section: Mekani̇k Venti̇lasyon Uygulanan Prematüre Bebeklere Pozi̇syon Vunclassified